Blackstone's Law Questions & answers - McKenzie, Susan (Blackstone Press, 1996)
The books cover all the essential topics found in undergraduate law degree courses, CPE courses and other undergraduate courses where law is an essential element. The books are divided by chapters covering each major topic, and contain up to 50 questions and answers. Each chapter has an introduction focusing on important legal aspects and points of interest, including suggestions for further reading. After each question there is a commentary which highlights the essential elements of each question, and indicates what the examiners are looking for